Urdu Writing Rules for Online Input in PDA’s - Fareeha Anwar; S. Afaq Husain (Linguistics and Literature Review, 2015)
For online input, stroke sequence based recognition is generally employed. For this method, the stroke sequence must be uniquely defined for every character/Ligature. Normally, every language has unique writing rules, which are followed by experienced users and recognition engines. However, there are variations in writing style from person to person and place to place. Languages which are written from right to left e.g. Urdu, Arabic, and Persian etc. are complex and have a lot of variations due to fonts and writing style. If rules are not followed properly, the recognition engine is bound to fail. Therefore, proper writing rules are necessary for online recognition of any language based on stroke sequence. There are no published and acknowledged rules available so far for Urdu language. This paper is an effort in accumulating writing rules for ‗ Nastalique‘ font for online Urdu recognition engine